Effect of Long-Term Marine -3 Fatty Acids Supplementation on the Risk of Atrial Fibrillation in Randomized Controlled Trials of Cardiovascular Outcomes: A Systematic Review and Meta-Analysis. Issue 25 (21st December 2021) - Gencer, Baris; Djousse, Luc; Al-Ramady, Omar T.; Cook, Nancy R.; Manson, JoAnn E.; Albert, Christine M.
Abstract : Background: Some, but not all, large-scale randomized controlled trials (RCTs) investigating the effects of marine -3 fatty acids supplementation on cardiovascular outcomes have reported increased risks of atrial fibrillation (AF). The potential reasons for disparate findings may be dose-related. Methods: The MEDLINE and Embase databases were searched for articles and abstracts published between January 1, 2012, and December 31, 2020, in addition to a meta-analysis of large cardiovascular RCTs published in 2019. RCTs of cardiovascular outcomes of marine -3 fatty acids that reported results for AF, either as a prespecified outcome, an adverse event, or a cause for hospitalization, with a minimum sample size of 500 patients and a median follow-up of at least 1 year were included. RCTs specifically examining shorter-term effects of -3 fatty acids on recurrent AF in patients with established AF or postoperative AF were not included. The hazard ratio (HR) for the reported AF outcomes within each trial was meta-analyzed using random effects model with Knapp-Hartung adjustment and evaluated a dose-response relationship with a meta-regression model. Results: Of 4049 screened records, 7 studies were included in the meta-analysis. Of those, 5 were already detected in a previous meta-analysis of cardiovascular RCTs. Among the 81 210 patients from 7 trials, 58 939 (72.6%) were enrolled in trials testing ⩽1 g/d and 22 271 (27.4%) in trials testing >1 g/d of -3 fatty acids. The mean age was 65 years, and 31 842 (39%) were female. The weighted average follow-up was 4.9 years. In meta-analysis, the use of marine -3 fatty acid supplements was associated with an increased risk of AF (n=2905; HR, 1.25 [95% CI, 1.07–1.46]; P =0.013). In analyses stratified by dose, the HR was greater in the trials testing >1 g/d (HR, 1.49 [95% CI, 1.04–2.15]; P =0.042) compared with those testing ⩽1 g/d (HR, 1.12 [95% CI, 1.03–1.22]; P =0.024; P for interaction <0.001). In meta-regression, the HR for AF increased per 1 g higher dosage of -3 fatty acids dosage (HR, 1.11 [95% CI, 1.06–1.15]; P =0.001). Conclusions: In RCTs examining cardiovascular outcomes, marine -3 supplementation was associated with an increased risk of AF. The risk appeared to be greater in trials testing >1 g/d. Abstract : Supplemental Digital Content is available in the text.